Perancangan Strategi Pemasaran Keripik Sukun dan Keripik Talas Di Home Industry Madani Metode SWOT dan QSPM - Akbar, Rahmad (Jurnal Sains dan Ilmu Terapan, 2023)
Home Industry Madani is a company engaged in the food industry of pineapple chips and jackfruit chips. Founded in January of 2010. Based on Background happened on Home Industry of Madani company issues that is not selling his solid performances jackfruit chips and pineapple chips are always decline at any period features. The number of products the pineapple chips sold in 2020 as much 16329 wrap, in 2021 as much 14011 wrap and in 2022 as much 11401 wrap. Jackfruit chips on sale while the number of products sold in 2020 as much 9277, 8037 as much in 2021 and in 2022 as much as 6850. The marketing strategy used Madani Home Industry at the moment is to use the promotion from the mouth – to the mouth. This research was conducted in order to identify and analyze the environmental factors internal and external company that affect marketing strategies on marketing pineapples and jackfruit chips Home Industry of Madani and designing marketing strategies using the SWOT method and the QSPM.